Crystallization and preliminary X-ray crystallographic study of a putative aspartyl-tRNA synthetase from the crenarchaeon Sulfolobus tokodaii strain 7 - Suzuki, Kaoru (International Union of Crystallography, 2007)
Genome analysis suggests that the aspartyl-tRNA synthetase of the crenarchaeon Sulfolobus tokodaii strain 7 belongs to the nondiscriminating type that is believed to catalyze aspartylation of tRNA(Asp) and tRNA(Asn). This protein has been overexpressed in Escherichia coli, purified and crystallized using the hanging-drop vapour-diffusion method from 100 mM sodium HEPES buffer pH 7.5 containing 100 mM NaCl and 1.6 M (NH(4))(2)SO(4) as the crystallizing reagent. Diffraction data were collected to 2.3 Å resolution using synchrotron radiation. The crystal belongs to the orthorhombic space group P2(1)2(1)2, with unit-cell parameters a = 116.0, b = 139.3, c = 75.3 Å. The estimated Matthews coefficient (3.10 Å(3) Da(−1); 60.3% solvent content) suggests the presence of two subunits in the asymmetric unit. The structure has been successfully solved by the molecular-replacement method. Full refinement of the structure may reveal it to be the original ancestor of the nondiscriminating AspRS.